2017
DOI: 10.1159/000481808
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Lead-Induced Neurotoxicity by Omega-3 Fatty Acid in Rats

Abstract: Background: Lead is widely distributed in the environment and has been found to be associated with various health problems including neurodegenerative diseases. Purpose: In view of the increasing health risk caused by lead, this study has been carried out to investigate the neuroprotective effect of omega-3 fatty acid (omega-3FA) in lead-induced neurotoxicity in rats. Methods: Biochemical parameters including oxidative stress in brain regions, lead levels in blood and brain regions and histopathological examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Additionally, hemorrhage, neurophagia and glial nodules were observed. These finding are agreement with those reported by (11,13,14) which they exposed mice, rats and guinea pigs to lead and observed Vascular lesions additionally to encephalpathic injury of lead mediated at the neuronal level.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, hemorrhage, neurophagia and glial nodules were observed. These finding are agreement with those reported by (11,13,14) which they exposed mice, rats and guinea pigs to lead and observed Vascular lesions additionally to encephalpathic injury of lead mediated at the neuronal level.…”
Section: Discussionsupporting
confidence: 93%
“…It is a potent neurotoxic agent, affecting nervous system (2,3). The brain tissue is vulnerable to the effects of lead injury (11,12). Lead is capable to pass through the endothelium of the blood brain barrier because it can replace for ions of the calcium and be taken up by Ca +2 -ATPase pumps, thus interfering with synapse formation.…”
Section: Discussionmentioning
confidence: 99%
“…LAT intoxication may also result in biochemical alterations and multiple neurological disorders such as AD, nerve damage, PD, damage to neuronal mitochondria, and finally leads to programmed cell death. [ 35 ] In our study, the results of serum and biochemical parameters obtained from animal samples suggested that LAT exposure is associated with increased AST, ALT, LDH, CPK, and ALP levels. Furthermore, an upregulation was also observed in oxidative stress (ROS), lipid peroxidation, protein carbonyl content, and apoptosis inducing factor Bax levels; on the other hand, a downregulation pattern was observed for superoxide dismutase, catalase, and glutathione peroxidase activities which highlighted the incidence of neurotoxicity.…”
Section: Resultsmentioning
confidence: 57%
“…[ 33,34 ] These outcomes are in agreement with the results reported in literature which suggests that LAT can accumulate in brain regions by crossing blood–brain barrier and express its toxic effects to cause AD. [ 33,35 ]…”
Section: Resultsmentioning
confidence: 99%
“…12,27 Exposure to lead acetate can increase free radicals in the body. 16,[28][29][30] Increased free radicals lead to a rise in lipid peroxidation, [31][32][33] one of the remaining lipid peroxidations often found is Malondialdehyde. [17][18][19] Previous research has shown that exposure to lead acetate leads to elevated levels of blood Malondialdehyde.…”
Section: Discussionmentioning
confidence: 99%